The Impact of Dengue on Liver Function as Evaluated by Aminotransferase Levels (Journal of Medicine, 2008)
Objective: To evaluate the impact of dengue virus infection on liver function by measuring aminotransferases in blood samples from patients serologically diagnosed as Dengue Fever. Background: Dengue, presenting as classical or haemorrhagic fever, also has some effect on liver function. This evaluation should be done for the management and deterination of prognosis of dengue with altered liver function. This study was done to find out the impact of dengue on liver function by evaluation of aminotransferase levels. Methods: Serologically confirmed 100 cases of dengue were included for the study. The patients were treated in the indoor. Informations were collected in a preformed revised structured questionnaire. Degree of liver involvement was classified in four grades according to Aminotransferase levels. Grades are as follows: Grade A - normal enzyme levels; Grade B - increased levels of at least one of the enzymes; Grade C - increased, with at least one of the enzymes being at levels higher than three times the upper reference values; Grade D - acute hepatitis, with aminotransferase levels at least ten times or more their upper limit of normal values. Results: Out of the confirmed dengue cases, 58% were female and 42% were male. Mean age was 34.5. 70% cases were classified as classic dengue and 30% as Dengue Haemorrhagic fever (DHF). Liver functions involvements were classified as Grade A in 34% cases, Grade B in 44% cases, Grade C in 20% cases and Grade D in 2% cases. High level of aminotransferases was 60% in classic dengue cases while it was 80% in DHF cases. Conclusion: Many of the dengue cases have abnormal liver function which are usually overlooked. This must be taken into account for risk stratification, management and prognosis of dengue cases. Keywords: Dengue, Classic Dengue, Dengue Haemorrhagic Fever, Dengue Shock Syndrome, Liver function, Aminotransferase. DOI = 10.3329/jom.v9i2.1432 Â Â  J MEDICINE 2008; 9 : 66-68